On integral manifolds of oscillating systems with slowly varying frequencies - Lakusta, L. M.; Petryshyn, R. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
By using averages of functions, we construct the integral manifold of an oscillating system that passes through resonances in the course of its evolution. We investigate the smoothness of the integral manifold and obtain estimates for its partial derivatives.